ANALISIS KINERJA RANTAI PASOK MENGGUNAKAN METODE BALANCED SCORECARD PADA PT. SUMBER ALFARIA TRIJAYA, TBK (ALFAMART) - Dewi Siti Khadijah; Yolanda Rizkyta Sari; Qurrotul Aini (Sistemasi: Jurnal Sistem Informasi, 2020)
Along with the development of the retail business, at this time the retail business is no longer managed traditionally, but in a modern way so that it becomes an innovative, dynamic, and competitive business. PT. Sumber Alfaria Trijaya, Tbk (Alfamart) is one of the retail businesses engaged in minimarket, which has grown to become one of the leading companies in the retail business. One effort to meet customer needs is to pay attention to supply chain management properly, because supply chain management basically pays attention to how the goods process gets into the hands of customers properly. The purpose of this research is to find out and analyze supply chain flow and performance, with the analytical method used is a balanced scorecard. Balanced scorecard translates a vision, mission, and strategy of the company into the determination of goals and scorecard size, balanced scorecard completes a set of financial measures of past performance with measures of drivers for future performance. The results of the average assessment recap with the balanced scorecard show that from a financial perspective it gets a value of 4 (good), an internal business process perspective gets a value of 4.15 (very good), a growth and development perspective gets a value of 3.8 (good), and a perspective customers get a value of 3.56 (good). It can be concluded that the performance of the supply chain at PT. Sumber Alfaria Trijaya, Tbk is already good, but still needs to be improved in order to be better.Keywords: Supply Chain, Balanced Scorecard, Alfamart.